Effect of Al2Cu precipitates size and mass transport on the polarisation behaviour of age-hardened Al–Si–Cu–Mg alloys in 0.05M NaCl - Vieira, A. C. (2011)
The electrochemical behaviour of age-hardened Al–Si–Cu–Mg alloys was investigated in a 0.05 M NaCl solution under controlled mass transport conditions using a rotating disk electrode. This work aimed at getting better understanding of the effect of the alloy microstructure, in particular the size distribution of Al2Cu phase, on the corrosion behaviour of the alloy. Three different size distributions of the Al2Cu phase were obtained through appropriate heat treatments. The cathodic reduction of oxygen was found to occur mainly on the Al2Cu phases acting as preferential cathodes. Small sized Al2Cu phases were found to promote at high rotation rates a transition from a 4 electron to a 2 electron dominated oxygen reduction mechanisms.